Current collector, pole piece using same and battery
By using acrylic modified polyurethane as a binder in the conductive layer of the current collector, the problem of poor adhesion between the current collector safety primer and the foil is solved, and the safety performance and puncture test pass rate of the lithium-ion battery are improved.
Patent Information
- Application Number
- CN202411296939.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-14
AI Technical Summary
The bonding force between the existing current collector safety primer and the foil is poor, resulting in a high probability of failure of lithium-ion batteries during puncture testing, and the safety performance of the battery cannot be fully guaranteed.
Acrylic modified polyurethane prepared from acrylic monomers, isocyanate monomers, and propylene glycol methyl ether acetate is used as a binder to form a conductive layer. The isocyanate groups in the conductive layer react with the carboxyl groups in the acrylic monomers. Chemical cross-linking improves the bonding force between the conductive layer and the foil.
It improves the bonding force between the conductive layer and the foil, enhances the flexibility and electrolyte resistance of the conductive layer, reduces the risk of the conductive layer falling off, and improves the safety performance and puncture test pass rate of lithium-ion batteries.
Smart Images

Figure BDA0005049128420000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a current collector, a pole piece and a battery using the current collector. Background Art
[0002] Lithium-ion batteries have been widely used in 3C electronic products, energy storage equipment, electric vehicles, and marine applications due to their many advantages, such as high energy density, high operating voltage, long cycle life, and low self-discharge. The popularity of electric vehicles has put forward higher requirements on the safety performance of lithium-ion batteries.
[0003] Existing data show that internal short circuits in lithium-ion batteries are the root cause of safety hazards in lithium-ion batteries. Among them, the internal short circuit caused by direct contact between the negative electrode and the positive electrode current collector aluminum foil is the most dangerous and prone to fire and explosion. In order to avoid internal short circuits in lithium-ion batteries, existing research has improved many aspects of lithium-ion batteries to improve the overall safety performance of lithium-ion batteries.
[0004] The existing methods of improving the safety performance of lithium-ion batteries are mainly divided into two categories. One is to add flame retardants to the electrode material or add flame retardant components to the electrolyte. The other is to apply a safety primer on the surface of the current collector, that is, to add a layer of safety coating between the electrode material layer and the current collector.
[0005] Chinese patent application CN 117913277 A discloses a lithium-ion battery safety primer slurry, a preparation method and application thereof, wherein graphene-modified lithium iron phosphate is used to replace part of the conductive carbon black, and then mixed with calcium hydroxide, a binder and deionized water to prepare a safety primer slurry. After coating and drying, a layer of safety primer is obtained. However, the binder type used in the safety primer is polyacrylate type, and the bonding strength between the primer and the foil needs to be improved.
[0006] At present, the commonly used binders for the safety primer of the current collector are mainly single-component water-based acrylic polymers, such as sodium polyacrylate, lithium polyacrylate, pure acrylic emulsion, styrene acrylic emulsion, etc. The safety primer prepared with this type of binder is generally poor in adhesion, flexibility and performance, and cannot completely guarantee that the coating and the foil are always firmly combined during puncture, thereby increasing the failure probability of the lithium-ion battery using it during the puncture test, and it is difficult to ensure the safety performance of the lithium-ion battery. Summary of the invention
[0007] In order to solve the problem of poor adhesion between the existing safety primer and foil of a current collector and improve the safety performance of a battery, the present invention provides a current collector, a pole piece and a battery using the same.
[0008] According to the first aspect of the present invention, a current collector is provided, which includes a foil and a conductive layer disposed on at least one surface of the foil, wherein the conductive layer includes a conductive agent, a binder and a dispersant; the binder is an acrylic modified polyurethane; the acrylic modified polyurethane includes an acrylic monomer, an isocyanate monomer and propylene glycol methyl ether acetate, and the molar ratio is calculated as follows: acrylic monomer: isocyanate monomer: propylene glycol methyl ether acetate monomer = 0.7-1.1: 0.1-0.2: 0.1-0.2. .
[0009] The existing safety primer of the current collector generally uses a single-component water-based acrylic polymer as a binder. The coating film-forming mechanism is non-conversion type, that is, physical drying film formation, which mainly relies on solvent evaporation and then drying film formation without any chemical cross-linking reaction. This physical film-forming safety coating is generally poor in adhesion, flexibility, and performance, and cannot completely guarantee that the coating and the aluminum foil are always firmly bonded during puncture, thereby increasing the failure probability of the battery cell using it during the puncture test.
[0010] Compared with the above-mentioned existing current collectors, the conductive layer (i.e., safety primer) on the foil surface of the current collector provided by the present invention adopts acrylic modified polyurethane made from acrylic monomers, isocyanate monomers, and propylene glycol methyl ether acetate as a binder. During the film formation process of the conductive layer on the foil surface, the isocyanate groups contained in the binder in the conductive layer will chemically cross-link with the carboxyl groups and other groups in the acrylic monomers, making the formed conductive layer denser, thereby improving the bonding force between the conductive layer and the foil, and at the same time giving the conductive layer excellent flexibility and resistance to electrolytes and solvents, reducing the risk of the conductive layer falling off during the actual application of the current collector, so that the conductive layer of the battery using the current collector provided by the present invention will not fall off during the puncture test, preventing the active substance from contacting the foil, and avoiding thermal runaway of the battery, thereby improving the safety performance of the battery. Moreover, compared with other polyether polyols, the present invention uses propylene glycol methyl ether acetate as a raw material for synthesizing acrylic modified polyurethane. Propylene glycol methyl ether acetate can be used as both a monomer and a solvent. Its molecular structure contains both ether bonds and carbonyl groups, and the carbonyl groups form an ester structure. There are both non-polar parts and polar parts in the same molecule. The functional groups of these two parts can both restrain and repel each other and play their own inherent roles. Therefore, it has a certain solubility for both non-polar substances and polar substances, which is beneficial to improving the coating strength of the conductive layer finally formed.
[0011] Preferably, the acrylic modified polyurethane comprises the following raw materials in parts by weight: 85-115 parts of acrylic monomer, 25-30 parts of isocyanate monomer, and 15-20 parts of propylene glycol methyl ether acetate.
[0012] Preferably, the acrylic modified polyurethane further comprises the following raw materials in parts by weight: 8 to 13 parts of end capping agent, 5 to 10 parts of chain extender, 45 to 55 parts of solvent, 0.1 to 0.8 parts of initiator, and 0.05 to 0.2 parts of catalyst.
[0013] Preferably, the acrylic acid ester monomer is prepared by mixing methyl methacrylate, butyl acrylate, acrylic acid and hydroxypropyl methacrylate in a mass ratio of 35-40:30-40:5-15:15-20.
[0014] Methyl methacrylate, butyl acrylate, acrylic acid, and hydroxypropyl methacrylate are compounded in the above-mentioned mass ratio as acrylic monomers and applied to the preparation of acrylic modified polyurethane. The prepared acrylic modified polyurethane is applied as a binder to the conductive layer of the current collector. The isocyanate groups contained in the binder will chemically cross-link with the carboxyl groups and hydroxyl groups in the acrylic monomers, which can further enhance the bonding strength between the conductive layer and the foil, thereby further reducing the risk of the current collector falling off during actual application.
[0015] Preferably, the isocyanate monomer includes at least one of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate.
[0016] Preferably, the isocyanate monomer is isophorone diisocyanate.
[0017] Preferably, the acrylic modified polyurethane is prepared by the following steps:
[0018] S1. The solvent is heated to 85 to 95°C, an acrylic monomer and an initiator are added dropwise to the solvent and kept at 85 to 95°C for 3 to 5 hours to obtain a first mixed solution;
[0019] S2. The isocyanate monomer and propylene glycol methyl ether acetate are mixed uniformly and heated to 40 to 50 ° C, and a capping agent is added dropwise thereto to obtain a second mixed solution;
[0020] S3. After the first mixed solution and the second mixed solution are evenly mixed and the catalyst is added, the reaction system is heated to 65 to 75 ° C and kept warm for 3 to 5 hours to obtain a third mixed solution;
[0021] S4. Add a chain extender to the third mixed solution, adjust the pH of the reaction system to 7-8, add water to disperse evenly, and obtain acrylic modified polyurethane.
[0022] The acrylic modified polyurethane involved in the present scheme is prepared by first using acrylic monomers and initiators to prepare a first mixed liquid containing polyacrylic acid prepolymer, and then using isocyanate monomers and propylene glycol methyl ether acetate to prepare a second mixed liquid containing a blocked polyurethane prepolymer, and after the first mixed liquid and the second mixed liquid react under the action of a catalyst, a chain extender is added to carry out a chain extension reaction, and the pH of the system is adjusted to 7-8 and water is added to disperse evenly to obtain the obtained product. The acrylic modified polyurethane prepared by the above method is applied as a binder to the conductive layer of the current collector, which can improve the bonding strength between the conductive layer and the foil and the flexibility of the current collector, ensure that the conductive layer and the foil of the battery cell using the current collector are always firmly bonded when punctured, and reduce the failure risk of the battery cell during the puncture test.
[0023] Preferably, in S1, the solvent comprises propylene glycol methyl ether acetate.
[0024] Preferably, in S1, the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and benzoyl peroxide.
[0025] Preferably, in S2, the blocking agent comprises methyl ethyl ketone oxime.
[0026] Preferably, in S3, the catalyst comprises dibutyltin dilaurate.
[0027] Preferably, in S4, the chain extender comprises dimethylethanolamine.
[0028] Preferably, the mass percentage of the above-mentioned binder in the conductive layer is 10-40%.
[0029] Preferably, the mass percentage of the above-mentioned binder in the conductive layer is 15-25%.
[0030] The content of the binder in the conductive layer of the current collector is controlled within the above range. Within this range, the binder content of the conductive layer is low, and the conductive layer still has good adhesion even at a lower binder dosage, so that the battery cell using the current collector will not catch fire or explode when punctured, thereby ensuring the safety performance of the battery cell.
[0031] Preferably, the conductive layer further comprises an inorganic material, and the mass percentage of the inorganic material in the conductive layer is 20-50%.
[0032] Preferably, the particle size of the inorganic material is D50<1.2 μm, D90<2.0 μm, and D99<2.9 μm.
[0033] By introducing inorganic materials into the conductive layer, the heat resistance of the conductive layer can be increased.
[0034] Preferably, the inorganic material includes at least one of boehmite, aluminum oxide, zirconium oxide and zinc oxide.
[0035] Preferably, the inorganic material is boehmite.
[0036] Boehmite is used as an inorganic material and introduced into the conductive layer of the current collector. On the one hand, the heat resistance of the conductive layer can be further improved. On the other hand, boehmite has flame retardant properties, which can delay combustion during puncture and reduce the temperature of the battery cell using the current collector, which is beneficial to improving the pass rate of the puncture test.
[0037] Preferably, the thickness of the conductive layer is 2-10 μm.
[0038] By controlling the thickness of the conductive layer of the current collector within the above range, while ensuring the bonding force between the conductive layer and the foil, the internal resistance of the battery cell using the current collector can be kept within an appropriate range, and the pass rate of the battery cell during the puncture test can be improved. If the thickness of the conductive layer of the current collector is too large, the internal resistance of the battery cell using the current collector will increase; if the thickness of the conductive layer of the current collector is too small, the puncture pass rate of the battery cell using the current collector will decrease.
[0039] Preferably, the thickness of the conductive layer is 5-7 μm.
[0040] Preferably, the conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, carbon fibers, and graphene.
[0041] Preferably, the dispersant includes at least one of sodium carboxymethyl cellulose, sulfate, sulfonate, and acrylate.
[0042] According to a second aspect of the present invention, a pole piece is provided, the pole piece comprising the above-mentioned current collector.
[0043] According to a third aspect of the present invention, a battery is provided, comprising the above-mentioned electrode sheet.
[0044] Applying the current collector provided by the present invention to pole pieces and batteries can improve the safety performance of the batteries and also extend the actual service life of the pole pieces and batteries. DETAILED DESCRIPTION
[0045] The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] A battery is prepared by the following steps:
[0048] 1. Preparation of positive electrode
[0049] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black, carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97.6:0.7:0.7:1, added into a solvent N-methylpyrrolidone (NMP), and mixed evenly to prepare a positive electrode slurry with a solid content of 45%, and the positive electrode slurry is coated on both surfaces of the positive electrode current collector, and a positive electrode sheet is prepared after baking and rolling;
[0050] The positive electrode current collector comprises an aluminum foil and a conductive layer disposed on two surfaces of the aluminum foil, and the positive electrode current collector is prepared by the following steps:
[0051] (1) Preparation of acrylic modified polyurethane binder
[0052] S1. In a flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, 50 parts by weight of propylene glycol methyl ether acetate solvent was added, the temperature was raised to 90°C, and a mixture containing 38 parts by weight of methyl methacrylate, 36 parts by weight of butyl acrylate, 10 parts by weight of acrylic acid, 18 parts by weight of hydroxypropyl methacrylate and 0.4 parts by weight of azobisisobutyronitrile was added dropwise to the flask at 90°C. The addition was completed within 3.5 hours, and the mixture was kept warm at 90°C for 4 hours, and then cooled to 70°C to obtain a first mixed solution, which was stored for later use;
[0053] S2. Take another flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, add 28 parts by weight of isophorone diisocyanate, 17 parts by weight of propylene glycol methyl ether acetate, under stirring, the temperature was raised to 45 ° C and 11 parts by weight of methyl ethyl ketone oxime was added dropwise to the flask, the addition was completed within 2.5 hours to obtain a second mixed solution;
[0054] S3. The first mixed solution stored in the standby state was added to the flask containing the second mixed solution, stirred evenly, 0.1 parts by weight of dibutyltin dilaurate T-12 was added, the temperature was raised to 70 ° C and kept warm for 4 hours to obtain a third mixed solution;
[0055] S4. Add 8 parts by weight of dimethylethanolamine to the flask containing the third mixed liquid, control the pH of the reaction system to 7-8, and finally add 100 parts by weight of deionized water, disperse and stir evenly, cool and discharge to obtain a closed acrylic modified polyurethane as a binder in the conductive layer of the positive electrode collector, wherein, in the acrylic modified polyurethane, calculated by molar ratio, methyl methacrylate monomer: butyl acrylate monomer: acrylic acid monomer: hydroxypropyl methacrylate monomer: isophorone diisocyanate monomer: propylene glycol methyl ether acetate monomer = 0.38:0.28:0.14:0.12:0.13:0.13.
[0056] (2) Preparation of positive electrode current collector containing conductive layer
[0057] The acrylic modified polyurethane binder, conductive carbon black (SP), inorganic boehmite particles, and dispersant sodium carboxymethyl cellulose (CMC) prepared above were mixed in a mass ratio of 25:5:67:3, and pure water solvent was added to prepare a conductive slurry with a solid content of 12%. The conductive slurry was coated on both surfaces of the aluminum foil by a gravure coater to form a conductive layer with a thickness of 5 μm, and baked at 140° C. for 20 minutes to obtain a positive electrode current collector containing a conductive layer, which is the positive electrode current collector used in the positive electrode sheet of this embodiment.
[0058] 2. Preparation of negative electrode
[0059] The negative electrode active material graphite, the conductive agent conductive carbon black (SP), the binder styrene-butadiene rubber (SBR), the dispersant sodium carboxymethyl cellulose (CMC), and the additive ethylene carbonate (EC) are mixed evenly in a mass ratio of 96:1.3:1.5:1.2:1.5, and then appropriate deionized water is added and dispersed evenly to obtain a negative electrode slurry with a solid content of 45%. The negative electrode slurry is coated on both surfaces of the carbon-coated copper foil, and after baking and rolling, a negative electrode sheet is obtained.
[0060] 3. Preparation of Diaphragm
[0061] Celgard 2400 diaphragm produced by Celgard Diaphragm Co., Ltd. of the United States is used.
[0062] 4. Preparation of Electrolyte
[0063] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1M.
[0064] 5. Battery Assembly
[0065] The positive electrode sheet and the negative electrode sheet are cut and sliced, and then wound with a separator to obtain a wound cell. The wound cell is packaged, baked, injected with electrolyte, formed, repackaged, and sorted to obtain a battery.
[0066] Example 2
[0067] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the acrylic acid-modified polyurethane binder used in the positive electrode current collector is different.
[0068] The olefin-modified polyurethane binder involved in this embodiment is prepared by the following steps:
[0069] S1. In a flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, 45 parts by weight of propylene glycol methyl ether acetate solvent was added, the temperature was raised to 85°C, and a mixed solution containing 35 parts by weight of methyl methacrylate, 40 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, 20 parts by weight of hydroxypropyl methacrylate and 0.1 parts by weight of azobisisobutyronitrile was added dropwise to the flask at 85°C. The addition was completed within 3.5 hours, and the mixture was kept warm at 85°C for 5 hours, and then cooled to 70°C to obtain a first mixed solution, which was stored for later use;
[0070] S2. Take another flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, add 25 parts by weight of isophorone diisocyanate, 15 parts by weight of propylene glycol methyl ether acetate, under stirring, the temperature was raised to 40 ° C and 8 parts by weight of methyl ethyl ketone oxime was added dropwise to the flask, the addition was completed within 2.5 hours to obtain a second mixed solution;
[0071] S3. The first mixed solution stored in the standby state was added to the flask containing the second mixed solution, stirred evenly, 0.05 parts by weight of dibutyltin dilaurate T-12 was added, the temperature was raised to 65 ° C and kept warm for 5 hours to obtain a third mixed solution;
[0072] S4. Add 5 parts by weight of dimethylethanolamine to the flask containing the third mixed liquid, control the pH of the reaction system to 7-8, and finally add 100 parts by weight of deionized water, disperse and stir evenly, cool and discharge to obtain a closed acrylic modified polyurethane as a binder in the conductive layer of the positive electrode collector, wherein, in the acrylic modified polyurethane, calculated by molar ratio, methyl methacrylate monomer: butyl acrylate monomer: acrylic acid monomer: hydroxypropyl methacrylate monomer: isophorone diisocyanate monomer: propylene glycol methyl ether acetate monomer = 0.35:0.31:0.07:0.14:0.11:0.11.
[0073] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0074] Example 3
[0075] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the preparation of the acrylic acid-modified polyurethane binder used in the positive electrode current collector is different.
[0076] The olefin-modified polyurethane binder involved in this embodiment is prepared by the following steps:
[0077] S1. In a flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, 55 parts by weight of propylene glycol methyl ether acetate solvent was added, the temperature was raised to 95°C, and a mixture containing 40 parts by weight of methyl methacrylate, 30 parts by weight of butyl acrylate, 15 parts by weight of acrylic acid, 15 parts by weight of hydroxypropyl methacrylate and 0.8 parts by weight of azobisisobutyronitrile was added dropwise to the flask at 95°C. The addition was completed within 3.5 hours, and the mixture was kept warm at 95°C for 3 hours, and then cooled to 70°C to obtain a first mixed solution, which was stored for later use;
[0078] S2. Take another flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, add 30 parts by weight of isophorone diisocyanate, 20 parts by weight of propylene glycol methyl ether acetate, under stirring, the temperature was raised to 50 ° C and 13 parts by weight of methyl ethyl ketone oxime was added dropwise to the flask, the addition was completed within 2.5 hours to obtain a second mixed solution;
[0079] S3. The first mixed solution stored in the standby state was added to the flask containing the second mixed solution, stirred evenly, 0.2 parts by weight of dibutyltin dilaurate T-12 was added, the temperature was raised to 75 ° C and kept warm for 3 hours to obtain a third mixed solution;
[0080] S4. Add 10 parts by weight of dimethylethanolamine to the flask containing the third mixed liquid, control the pH of the reaction system to 7-8, and finally add 100 parts by weight of deionized water, disperse and stir evenly, cool and discharge to obtain a closed acrylic modified polyurethane as a binder in the conductive layer of the positive electrode collector, wherein, in the acrylic modified polyurethane, calculated by molar ratio, methyl methacrylate monomer: butyl acrylate monomer: acrylic acid monomer: hydroxypropyl methacrylate monomer: isophorone diisocyanate monomer: propylene glycol methyl ether acetate monomer = 0.4: 0.23: 0.21: 0.1: 0.13: 0.15.
[0081] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0082] Example 4
[0083] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the acrylic acid-modified polyurethane binder, an equal amount of acrylic acid is used to replace hydroxypropyl methacrylate. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0084] Example 5
[0085] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that in the preparation step S1 of the acrylic acid-modified polyurethane binder, an equal amount of acrylic acid is used to replace butyl acrylate. Except for the above difference, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0086] Example 6
[0087] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the mass ratios of various materials in the acrylic monomers used in the preparation step S1 of the acrylic modified polyurethane binder are different.
[0088] The acrylic monomers used in this embodiment include 30 parts by weight of methyl methacrylate, 36 parts by weight of butyl acrylate, 20 parts by weight of acrylic acid, and 18 parts by weight of hydroxypropyl methacrylate.
[0089] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0090] Example 7
[0091] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the mass ratios of various materials in the acrylic monomers used in the preparation step S1 of the acrylic modified polyurethane binder are different.
[0092] The acrylic monomers used in this embodiment include 38 parts by weight of methyl methacrylate, 36 parts by weight of butyl acrylate, 20 parts by weight of acrylic acid, and 10 parts by weight of hydroxypropyl methacrylate.
[0093] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0094] Example 8
[0095] This embodiment provides a battery. Compared with the embodiment 1, the difference in structure is that the preparation method of the acrylic modified polyurethane binder used in the positive electrode current collector is different.
[0096] The acrylic acid modified polyurethane binder used in this embodiment is prepared by the following steps:
[0097] S1. In a flask equipped with a stirring device, a thermometer, a constant pressure dropping funnel and a reflux condenser, 28 parts by weight of isophorone diisocyanate, 17 parts by weight of propylene glycol methyl ether acetate, 11 parts by weight of methyl ethyl ketone oxime, 50 parts by weight of butanone were added, and the temperature was raised to 70°C under stirring, and 0.1 parts by weight of dibutyltin dilaurate T-12 was added dropwise to the flask, and the addition was completed within 2.5 hours, the temperature was maintained at 70°C, and stirring was continued for 3 hours to obtain a prepolymer;
[0098] S2. Add a mixed solution containing 38 parts by weight of methyl methacrylate, 36 parts by weight of butyl acrylate, 10 parts by weight of acrylic acid and 18 parts by weight of hydroxypropyl methacrylate into the flask containing the above-mentioned prepolymer, raise the temperature to 70°C, add 0.4 parts by weight of azobisisobutyronitrile into the flask, keep warm at 70°C for 6 hours, cool and discharge the material to obtain a closed acrylic modified polyurethane.
[0099] Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in Example 1.
[0100] Example 9
[0101] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the mass ratio of the acrylic modified polyurethane binder, the conductive agent SP, the inorganic particle boehmite, and the dispersant CMC used in the preparation method of the positive electrode current collector is 15:5:77:3. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0102] Example 10
[0103] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the mass ratio of the acrylic modified polyurethane binder, the conductive agent SP, the inorganic particle boehmite, and the dispersant CMC used in the preparation method of the positive electrode current collector is 35:5:57:3. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0104] Embodiment 11
[0105] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the thickness of the conductive layer in the positive electrode current collector is 10 μm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0106] Example 12
[0107] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the thickness of the conductive layer in the positive electrode current collector is 2 μm. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0108] Embodiment 13
[0109] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the mass ratio of the acrylic modified polyurethane binder, the conductive agent SP, the inorganic particle boehmite, and the dispersant CMC used in the preparation method of the positive electrode current collector is 25:3:67:3. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0110] Embodiment 14
[0111] This embodiment provides a battery, and compared with the embodiment 1, the difference in structure is that the conductive layer does not contain inorganic boehmite particles, and in the preparation step of the positive electrode current collector containing the conductive layer, the mass ratio of the acrylic modified polyurethane binder, the conductive agent SP, and the dispersant CMC is 25:5:70. Except for the above differences, the materials, formula ratios, and preparation operations used in this embodiment are strictly consistent with those in the embodiment 1.
[0112] Comparative Example 1
[0113] This comparative example provides a battery, which is different from Example 1 in that in the preparation process of the positive electrode current collector, an equal amount of conventional water-based acrylic binder (purchased from Fujian Blue Sea Black Stone New Material Technology Co., Ltd., brand BC-602) is used to replace the acrylic modified polyurethane binder. Except for the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0114] Comparative Example 2
[0115] This comparative example provides a battery, and compared with Example 1, the difference in structure is that the positive electrode current collector used in the preparation process of the positive electrode sheet is pure aluminum foil without a conductive layer. Except for the above difference, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.
[0116] Test Case
[0117] 1. Participants
[0118] In this test example, the positive electrode current collectors and batteries prepared in Examples 1 to 14 and Comparative Examples 1 to 2 were used as test objects to conduct relevant performance tests.
[0119] 2. Test content
[0120] (1) Peel force test
[0121] Use 3M610 tape (3M Scotch 610 tape) to evenly adhere the tape to the surface of the conductive layer of the positive electrode current collector, use a 1kg pressure wheel to roll three times, pull the tape 180°, and observe the peeling state of the conductive layer of the positive electrode current collector. The judgment criteria are as follows:
[0122] “Level 0” means that the conductive layer is intact and there is no falling off area;
[0123] "Level 1" means that the conductive layer is very slightly detached and the affected area is less than 5%;
[0124] "Level 2" means that the conductive layer is partially detached, and the affected area is 5-25%;
[0125] "Level 3" means that the conductive layer is more detached, and the affected area is 25-65%;
[0126] "Level 4" means that the conductive layer falls off over a large area, with the affected area being 65-95%;
[0127] "Level 5" means that the conductive layer is almost completely detached and the affected area is greater than 95%.
[0128] (2) Electrolyte resistance
[0129] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a lithium salt concentration of 1M; take a cotton swab, wet the cotton swab with the prepared electrolyte, and then wipe the cotton swab on the conductive layer of the positive electrode current collector. Wiping back and forth counts as one time, and the number of wiping when the conductive layer fades or falls off is recorded.
[0130] (3) Solvent resistance
[0131] Take a cotton swab, wet it with solvent N-methylpyrrolidone (NMP), and then wipe the cotton swab on the conductive layer of the positive electrode current collector. Wipe back and forth once, and record the number of wipes when the conductive layer fades or falls off.
[0132] (4) Battery internal resistance
[0133] Charge the battery to full charge, use a voltage resistance meter to test the internal resistance of the battery cell and record it.
[0134] (5)Puncture test
[0135] Charge the battery to full charge, and use a battery cell puncture test machine with a steel nail of 3 mm in diameter to pierce the middle of the front of the battery cell at a rate of 150 mm / s. Keep it for 6 hours. The battery is qualified if it does not catch fire or explode. Calculate the puncture pass rate according to the following formula: Puncture pass rate (%) = number of batteries that pass the puncture test / total number of tested batteries × 100%.
[0136] 3. Experimental results
[0137] Table 1. Test results of positive electrode current collector and battery performance
[0138]
[0139] The relevant performance test results of the positive electrode current collectors and batteries prepared in Examples 1 to 14 and Comparative Examples 1 to 2 are shown in Table 1.
[0140] In Examples 1 to 14 and Comparative Examples 1 to 2, the positive electrode current collector provided in Comparative Example 2 has no safety primer, i.e., does not contain a conductive layer. The test results show that 100% of the batteries using the positive electrode current collector provided in Comparative Example 2 caught fire and exploded during the puncture test, which indicates that the conductive layer in the positive electrode current collector has a significant effect on improving the safety performance of the battery.
[0141] Compared with Comparative Example 1, the conductive layer in the positive current collector provided by Examples 1 to 14 adopts acrylic modified polyurethane made from acrylic monomers, isocyanate monomers and propylene glycol methyl ether acetate as a binder. The test results show that the peeling force between the conductive layer and the foil of the positive current collector provided by Examples 1 to 14 is higher than that of Comparative Example 1, and the electrolyte resistance and solvent resistance are better than those of Comparative Example 1. The puncture pass rate of the battery using the positive current collector provided by Examples 1 to 14 is higher than that of Comparative Example 1. The reason for the above phenomenon is that the conductive layer (i.e., safety primer) on the surface of the foil of the current collector provided in Examples 1 to 14 uses acrylic modified polyurethane prepared from acrylic monomers, isocyanate monomers, and propylene glycol methyl ether acetate as a binder. During the film formation process of the conductive layer on the surface of the foil, the isocyanate group contained in the binder in the conductive layer will chemically cross-link with the carboxyl group and other groups in the acrylic monomer, making the formed conductive layer denser, thereby improving the bonding force between the conductive layer and the foil, and at the same time giving the conductive layer excellent flexibility and electrolyte and solvent resistance, reducing the risk of the conductive layer falling off during the actual application of the current collector, so that the conductive layer of the battery using the current collector provided by the present invention will not fall off during the puncture test, preventing the active substance from contacting the foil, and avoiding thermal runaway of the battery, thereby improving the safety performance of the battery.
[0142] Compared with Example 1, the raw material acrylic monomer for preparing the acrylic modified polyurethane binder in the conductive layer of the positive current collector provided in Example 4 does not contain hydroxypropyl methacrylate, and the raw material acrylic monomer for preparing the acrylic modified polyurethane binder in the conductive layer of the positive current collector provided in Example 5 does not contain butyl acrylate. The test results show that the electrolyte resistance and solvent resistance of the positive current collectors provided in Examples 4 to 5 are worse than those in Example 1, and the internal resistance of the battery using the positive current collectors provided in Examples 4 to 5 is higher than that in Example 1; the raw material acrylic monomer for preparing the acrylic modified polyurethane binder in the conductive layer of the positive current collector provided in Example 6 consists of methyl methacrylate, butyl acrylate, , acrylic acid, and hydroxypropyl methacrylate are mixed in a mass ratio of 30:36:20:18. The acrylic monomer as a raw material for preparing the acrylic modified polyurethane bonding agent in the conductive layer of the positive current collector provided in Example 7 is mixed with methyl methacrylate, butyl acrylate, acrylic acid, and hydroxypropyl methacrylate in a mass ratio of 38:36:20:10. The test results show that the electrolyte resistance, solvent resistance, peeling force between the conductive layer and the foil of the positive current collector provided in Examples 6-7 and the puncture pass rate of the battery using the positive current collector provided in Examples 6-7 are worse than those in Example 1, and the internal resistance of the battery using the positive current collector provided in Examples 6-7 is higher than that in Example 1.
[0143] The difference between Example 1, Example 9 and Example 10 is that the content of the acrylic modified polyurethane binder in the conductive layer of the positive electrode current collector is different. The test results show that even at a lower dosage of the acrylic modified polyurethane binder, the conductive layer and the foil still have good adhesion, and the battery using the above positive electrode current collector does not catch fire or explode during the puncture test.
[0144] The difference between Example 1, Example 11 and Example 12 is that the thickness of the conductive layer of the positive current collector is different. The test results show that as the thickness of the conductive layer of the positive current collector increases, the internal resistance of the battery using the positive current collector will increase, but when the thickness of the conductive layer is low, it will affect the puncture pass rate of the battery.
[0145] The test results of Example 1 and Example 13 show that the less the conductive agent content in the conductive layer of the positive electrode current collector, the greater the internal resistance of the battery using the positive electrode current collector, but both of them did not catch fire or explode during the puncture test.
[0146] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A current collector, characterized in that: The current collector includes a foil and a conductive layer disposed on at least one surface of the foil, wherein the conductive layer includes a conductive agent, a binder and a dispersant; The binder is acrylic acid modified polyurethane; The acrylic modified polyurethane comprises acrylic monomers, isocyanate monomers and propylene glycol methyl ether acetate monomers, and the molar ratio of the acrylic monomers: the isocyanate monomers: the propylene glycol methyl ether acetate monomers is 0.7-1.1: 0.1-0.2: 0.1-0.
2.
2. The current collector according to claim 1, characterized in that: The acrylic acid ester monomer is prepared by mixing methyl methacrylate, butyl acrylate, acrylic acid and hydroxypropyl methacrylate in a mass ratio of 35-40:30-40:5-15:15-20.
3. The current collector according to claim 1, characterized in that: The isocyanate monomer includes at least one of isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate and hexamethylene diisocyanate.
4. The current collector according to claim 1, characterized in that: The acrylic acid modified polyurethane is prepared by the following steps: S1. The solvent is heated to 85 to 95°C, the acrylic monomer and the initiator are added dropwise to the solvent and kept at 85 to 95°C for 3 to 5 hours to obtain a first mixed solution; S2. The isocyanate monomer and the propylene glycol methyl ether acetate are mixed uniformly and heated to 40 to 50° C., and a capping agent is added dropwise thereto to obtain a second mixed solution; S3. After the first mixed solution and the second mixed solution are evenly mixed and the catalyst is added, the reaction system is heated to 65 to 75 ° C and kept warm for 3 to 5 hours to obtain a third mixed solution; S4. Add a chain extender to the third mixed solution, adjust the pH of the reaction system to 7-8, add water to disperse evenly, and obtain the acrylic modified polyurethane.
5. The current collector according to claim 4, characterized in that: In S1, the solvent includes propylene glycol methyl ether acetate, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, and benzoyl peroxide; In S2, the end-capping agent includes methyl ethyl ketone oxime; In S3, the catalyst includes dibutyltin dilaurate; In the S4, the chain extender includes dimethylethanolamine.
6. The current collector according to claim 1, characterized in that: The mass percentage of the binder in the conductive layer is 10-40%.
7. The current collector according to claim 1, characterized in that: The conductive layer further comprises an inorganic material, and the mass percentage of the inorganic material in the conductive layer is 20 to 50%; The particle size of the inorganic material is D50<1.2μm, D90<2.0μm, and D99<2.9μm; The inorganic material includes at least one of boehmite, aluminum oxide, zirconium oxide and zinc oxide.
8. The current collector according to claim 1, characterized in that: The thickness of the conductive layer is 2-10 μm.
9. A pole piece, characterized in that: The pole piece includes the current collector as claimed in any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the electrode piece as claimed in claim 9.
Citation Information
Patent Citations
Safety prime coat slurry for lithium ion battery as well as preparation method and application of safety prime coat slurry
CN117913277A
Polyurethane / polycarboxylic acid compound water reducer for concrete and preparation thereof
CN101734879A
Polyurethane cured acrylic resin anti-fogging and abrasion-resistant paint and preparation method thereof
CN102086348A
Urethane-acrylate copolymer and photoresist composition thereof
CN104817656A
Novel formaldehyde removal anti-microbial water-based UV paint
CN105694706A